Investigation of Waste Perlite and Recycled Concrete Powders as Supplementary Cementitious Materials - Dacić, Amina; Fenyvesi, Olivér; Kopecskó, Katalin (Periodica Polytechnica Civil Engineering, 2023)
One of the sustainable solutions for cementitious materials could be the inclusion of locally available raw materials with possible lower environmental and/or economic impacts that meet technical requirements. This study focuses on waste perlite and recycled concrete powders, which are wastes from natural or artificial rock. Their effects on hardened and fresh properties were investigated by cement replacement of 15, 30 and 45 m%. The waste perlite powders demonstrated higher reactivity, while the recycled concrete powder would act mainly as a filler material. When using recycled concrete and waste perlite powders, an adverse effect was identified on the examined fresh properties.